2023
DOI: 10.1113/jp283719
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs – small RNAs with a big influence on brain excitability

Abstract: MicroRNAs are non‐coding RNAs, approximately 22 nt in length, which serve to negatively regulate gene expression through binding to complementary sequences in the 3′ untranslated region (3′UTR) of target mRNA. The microRNA–target interaction does not require perfect complementarity, meaning that an individual microRNA often has a pool of hundreds of gene targets. Equally, one 3′UTR can contain target sites for many different microRNAs. This gives rise to a complex web of molecular interactions. An emerging con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The World Health Organization (WHO) classification, primarily based on morphological parameters, has yet to suggest changes in the grading of meningiomas despite significant advances in understanding the molecular mechanisms of tumorigenesis and meningioma progression [ 7 ]. However, the analysis of chromosomal regions and the study of new genes are expected to contribute to future diagnosis and prognosis [ 8 ]. Molecular markers may eventually facilitate the combination of histological and molecular criteria in the classification of meningiomas [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) classification, primarily based on morphological parameters, has yet to suggest changes in the grading of meningiomas despite significant advances in understanding the molecular mechanisms of tumorigenesis and meningioma progression [ 7 ]. However, the analysis of chromosomal regions and the study of new genes are expected to contribute to future diagnosis and prognosis [ 8 ]. Molecular markers may eventually facilitate the combination of histological and molecular criteria in the classification of meningiomas [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to imperfect base pairing between miRNAs and their mRNA targets, an individual miRNA can repress many different mRNAs, and individual mRNAs can be targeted by multiple miRNAs 10 13 . This multi-targeting property is appealing for anti-epileptogenesis therapy 14 or for treating the complex and multifaceted pathophysiology of temporal lobe epilepsy (TLE), a highly pharmacoresistant epilepsy 15 . Indeed, many of the dysregulated gene networks in TLE are known or predicted targets of miRNAs and there is also extensive dysregulation of miRNA levels in experimental and human TLE 16 21 .…”
Section: Introductionmentioning
confidence: 99%
“…As miRNAs regulate multiple gene pathways simultaneously ( 12 ), they are an attractive target in the treatment of epilepsy where complex and diverse mechanisms give rise to imbalances between excitation and inhibition ( 13 ). This includes modulating the expression of voltage-gated ion channels ( 14 , 15 ). For example, Sosanya et al reported that miR-129 regulated the expression of Kcna1 , encoding the voltage-gated potassium channel K V 1.1 ( 16 ).…”
mentioning
confidence: 99%